No-Touch Sequential Saphenous Venous Harvesting Technique in Off-Pump Bypass Surgery: A Retrospective Study - Hou, Xuejian; Zhang, Kui; Liu, Taoshuai; Li, Yang; Zhao, Yang; Song, Bangrong; Huang, Zhuhui; Zheng, Jubing; Dong, Ran (Frontiers in Cardiovascular Medicine, 2022)
Background In the mid-1990s, the Swedish expert team proposed saphenous vein graft (SVG) harvesting with pedicle tissue. The short-term and long-term patency rates of the great saphenous vein obtained by the no-touch (NT) were higher than those obtained by the conventional (CON). In the past, NT harvesting was mainly used in on-pump coronary artery bypass grafting (CABG), and vein grafts were mostly single vein grafts. In this study, we retrospectively analyzed the safety and effectiveness of sequential vein grafts using NT harvesting in off-pump CABG. Methods From 2017 to 2019, a total of 505 patients were included in the study. There were 150 patients in the NT group and 355 patients in the CON group. After applying propensity score matching (1:1 matching), 148 patients were included in each group. Baseline data, graft patency, post-operative complications, leg wound complications and 1-year major adverse cardiac and cerebrovascular events (MACCEs) were compared between the two groups. Results There was no significant difference in the patency rate of sequential venous grafts between the two groups 1 year after the operation either before [NT: 7.1% (10/141) vs. CON: 11.5% (38/331), p = 0.149) or after matching (NT: 7.1% (10/140) vs. CON: 7.3% (9/124), p = 0.971]. There was no significant difference in the composite clinical endpoint between the two groups either before [NT: 3 (2.3%) vs. CON: 9 (2.8%), p = 1.000] or after matching [NT: 3 (2.3%) vs. CON: 3 (2.5%), p = 1.000]. There were differences in leg wound complications between the two groups both before [NT: 9 (6.9%) vs. CON: 6 (1.9%), p = 0.007] and after matching [NT: 9 (6.9%) vs. CON: 2 (1.7%), p = 0.043]. Conclusions The application of the NT harvesting in off-pump CABG with sequential vein grafts is safe and effective. NT method has disadvantages in leg wound.